Age-Varying Association Between Blood Pressure and Risk of Dementia in Those Aged 65 and Older: A Community-Based Prospective Cohort Study - Li, Ge; Rhew, Isaac C.; Shofer, Jane B.; Kukull, Walter A.; Breitner, John C. S.; Peskind, Elaine; Bowen, James D.; McCormick, Wayne; Teri, Linda; Crane, Paul K.; Larson, Eric B. (Journal of the American Geriatrics Society (JAGS), 2007)
OBJECTIVES: To assess variation in the association between blood pressure (BP) and risk for dementia across a spectrum of older ages and to examine BP changes before dementia onset. DESIGN: Prospective cohort study. SETTING: A large health maintenance organization in Seattle, Washington. PARTICIPANTS: A cohort of 2,356 members of a large health maintenance organization aged 65 and older who were initially without dementia. MEASUREMENTS: Dementia diagnosis was assessed biennially, and systolic (SBP) and diastolic BP (DBP) were measured at baseline and at four follow‐up assessments. Cox proportional hazards models were used to estimate hazard ratios (HRs) for dementia and Alzheimer's disease (AD) associated with baseline BP in different age groups. RESULTS: Within the youngest age group (65–74 at enrollment) a greater risk for dementia was found in participants with high SBP (≥160 mmHg) (hazard ratio (HR)=1.60, 95% confidence interval (CI)=1.01–2.55) or borderline‐high DBP (80–89 mmHg) (HR=1.59, 95% CI=1.07–2.35) than for those with normal BP (SBP <140 mmHg and DBP <80 mmHg). The dementia risk associated with SBP declined with increasing age (SBP‐by‐age interaction, P=.01). SBP declined similarly with aging in subjects who developed dementia and those who did not. Thus, in this sample, the association between SBP and dementia risk was not dependent on when BP was measured in relation to onset of dementia. CONCLUSION: High SBP was associated with greater risk of dementia in the young elderly (<75) but not in older subjects. Adequate control of hypertension in early old age may reduce the risk for dementia.